Factors for manufacturing competitiveness of automotive part suppliers from Nuevo Leon, Mexico: a literature review - Valdez de la Rosa, Luz María; Villarreal Villarreal, Luis Alberto; Garza Villegas, Juan Baldemar (IEOM Society International, 2017)
The automotive industry represents one of the most important industries for the economic growth of Mexico. In the last seven years, Mexico has reached the tenth place among the worldwide producers of light automobiles and became an important automotive part supplier. It contributes with 3.5% of the world production. Nuevo Leon takes part of the cluster of automotive parts suppliers with the higher importance for the country. By using a systematic literature review, obtained from data bases of two universities, University of Monterrey (UDEM) and Autonomous University of Nuevo Leon (UANL), the present research finds six factors with high impact to the manufacturing competitiveness of the automotive parts suppliers, in the automotive industry. These are: quality, product innovation, process technology, qualified capital human, support of the automotive cluster, and information technology. In scientific research a relevant issue is measurement. Factors that form part of the measurement process are discussed. This study presents an analysis of each one of these factors, and how they have an impact to the manufacturing competitiveness of the automotive industry